Isolable Geminal Bisgermenolates: A New Synthon in Organometallic Chemistry. (28th September 2021) - Drusgala, Manfred; Frühwirt, Philipp; Glotz, Gabriel; Hogrefe, Katharina; Torvisco, Ana; Fischer, Roland C.; Wilkening, H. Martin R.; Kelterer, Anne‐Marie; Gescheidt, Georg; Haas, Michael
Abstract: We have synthesized the first isolable geminal bisenolates L2 K2 Ge[(CO)R]2 ( R =2, 4, 6‐trimethylphenyl (2 a, b ), L=THF for (2 a ) or [18]‐crown‐6 for (2 b )), a new synthon for the synthesis of organometallic reagents. The formation of these derivatives was confirmed by NMR spectroscopy and X‐ray crystallographic analysis. The UV/Vis spectra of these anions show three distinct bands, which were assigned by DFT calculations. The efficiency of 2 a, b to serve as new building block in macromolecular chemistry is demonstrated by the reactions with two different types of electrophiles (acid chlorides and alkyl halides). In all cases the salt metathesis reaction gave rise to novel Ge‐based photoinitiators in good yields. Abstract : A convenient method to obtain geminal bisenolates L2 K2 Ge[(CO)R]2 ( R =2, 4, 6‐trimethylphenyl (1 a, b ), L=THF for (1 a ) or [18]‐crown‐6 for (1 b )), a new synthon for the synthesis of organometallic reagents, is reported. Selected examples of electrophiles were used to display the efficiency of 1 a, b as new building blocks in organometallic chemistry.